Personality Accounts for the Connection Between Volunteering and Health - King, Hannah R. (J Gerontol B Psychol Sci Soc Sci, 2015)
OBJECTIVES. Existing literature has shown that volunteering is related to better physical and mental health outcomes. The purpose of this study is to examine whether personality traits and volunteering are independent predictors of physical and mental health. METHODS. The current study utilizes data from the St. Louis Personality and Aging Network (SPAN), a representative sample of community-based adults between the ages of 55 and 64. Using hierarchical linear regressions, we test whether volunteering is a significant predictor of both physical and mental health while controlling for personality traits. RESULTS. We find that volunteering is not significantly related to either physical or mental health while controlling for personality traits. We also find that lower neuroticism is related to better physical functioning and mental health, whereas higher extraversion is related to better mental health. DISCUSSION. These results indicate that volunteering may be related to health outcomes because of the personality characteristics of volunteers, not the volunteering experience in and of itself. Future longitudinal studies are needed to further explore the relationship between personality, volunteering, and health.